The Analysis of Rural Road Distress with Indonesian Standard: A Case of Majalengka-West Java - Muhammad N. F. A. Rachman; Andri Irfan Rifai; Arief Rijaluddin; Joewono Prasetijo (Engineering Proceedings)
Road connectivity and accessibility for the community start from the lowest level, namely rural roads. Rural road conditions reflect the condition of infrastructure in rural areas. This study aims to study the characteristics of rural road damage. The location of this study is rural roads in West Java, Indonesia, the case of Majalengka Regency. Data collection was carried out on Jalan Gunung Kuning-Sindang in May 2024. The research method and data processing used the Bina Marga–Indonesia (Directorate General of Highway) standard. The study results show that, in general, the rural roads are still damaged. Most of the damage to these village roads is due to poor road maintenance and water control along the road, especially in mountainous areas. Based on the priority order, a value of 9 was obtained to be included in the periodic maintenance program.